Ontologi Tasawuf Falsafi dalam Konsep Wahdatul Wujud Ibnu Arabi - Kamaruddin Mustamain (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2020)
Ibn Arabi's wahdatul wujud concept, which has tended to be trapped in a static understanding of a unified existence between the Creator and the one created in the locus of pantheism must be understood as an active movement in which beings who are in the levels of selfhood must always strive to move actively towards the levels of reality. This has implications for the need to develop a more inclusive understanding in understanding metaphorical-sufistic language which seems foreign to ordinary people. The ontology of philosophical tasawuf in Ibn Arabi's wahdatul wujud concept has provided a methodological framework that emerged from the sitesis of two different scientific groups, namely Sufism with its esoteric dimension and philosophy with its philosophical dimension in uncovering the meaning of Ibn Arabi's wahdatul wujud concept.